Automate and Orchestrate Your IBM FlashSystem Hybrid Cloud with Red Hat Ansible Version 1 Release 1 - IBM (IBM Redbooks, 2020)
This document is intended to facilitate the deployment of Red Hat Ansible for the IBM FlashSystem®. The document describes the automation and orchestration of storage provisioning for the IBM FlashSystem by using Red Hat Ansible. To complete the tasks that are described in this document, you must understand the IBM FlashSystem and Red Hat Ansible. The information in this document is distributed on an "as-is" basis without any warranty that is either expressed or implied. Support assistance for the use of this material is limited to situations where IBM FlashSystem storage devices are supported and entitled, and where the issues are specific to a blueprint implementation